Celecoxib enhances the therapeutic efficacy of epirubicin for Novikoff hepatoma in rats. (23rd April 2018) - Chu, Tian‐Huei; Chan, Hoi‐Hung; Hu, Tsung‐Hui; Wang, E‐Ming; Ma, Yi‐Ling; Huang, Shih‐Chung; Wu, Jian‐Ching; Chang, Yi‐Chen; Weng, Wen‐Tsan; Wen, Zhi‐Hong; Wu, Deng‐Chyang; Chen, Yi‐Ming Arthur; et al.
Abstract: Epirubicin is a chemotherapy agent for hepatocellular carcinoma (HCC). However, the outcome of HCC patients receiving epirubicin remains unsatisfactory. Moreover, our previous study indicated that celecoxib suppresses HCC progression and liver cancer stemness. This study evaluated the potential of celecoxib to serve as a complementary therapy during epirubicin treatment. Cell proliferation, apoptosis, invasiveness, and anchorage‐independent growth were analyzed in hepatoma cells. Therapeutic efficacy was validated in rat orthotopic Novikoff hepatoma. After animal sacrifice, the antitumor mechanism of celecoxib and epirubicin combined therapy was investigated by histological analysis. Celecoxib enhanced the cytotoxic activity of epirubicin in HCC cells by promoting apoptosis. Besides, celecoxib potentiated the antineoplastic function of epirubicin in inhibiting the invasiveness and anchorage‐independent growth of HCC cells. Ultrasound monitoring showed that combined therapy was more potent than either therapy alone in perturbing HCC progression. Consistently, the size and weight of dissected HCC tissues from rats receiving combined therapy were smallest among all groups. HCC treated with combined therapy exhibited the highest prevalence of apoptotic cells, which was accompanied by reduced proliferating and angiogenic activities in tumor tissues. Moreover, the expression levels of cancer stemness markers (CD44 and CD133) and drug transporter MDR‐1 were significantly diminished in rats receiving combined therapy. Besides, celecoxib treatment increased the infiltration of cytotoxic T lymphocytes (CTLs) and reduced the number of regulatory T cells (Tregs), tumor‐associated macrophages (TAMs), and the expression of immune checkpoint PD‐L1 in HCC tissues during epirubicin therapy. Celecoxib augmented the therapeutic efficacy while modulated cancer stemness and antitumor immunity. Thus, celecoxib may serve as complementary therapy to improve the outcome of patients with advanced HCC during epirubicin treatment. Abstract : Celecoxib potentiates therapeutic efficacy of epirubicin for advanced liver cancer. Celecoxib modulates liver cancer stemness and antitumor immunity.